RANCANG BANGUN SISTEM INFORMASI PEMASARAN PROPERTI BERBASIS WEB DIKOTA BATAM - Damanik, Setiawati; Rasid Ridho, Muhammat (Computer Science and Industrial Engineering, 2022)
Property marketing is one of the many businesses interested by businesses in batam city. As the age developed the use of information technology is very influenced on all aspects, including aspects of property marketing business. With the presence of technology and this information can help Solving problems and work to be more efficient and effective. By building a web-based property marketing information system will be helping property marketing in batam city to be more effective and efficiently used to market property. In this research the process was performed to collect data used by the author is by observation techniques and interviewing property owners to get information to know the specifications of the property that is marketed or for sale. The system design method used is the water fall method where the stages are Requirements definition, system software and design, implementation and unit testing, integration and system testing, operation and maintenance. With the development of this information system it is hope to easy property owners to market their property and communities who will be buyers easy to know accurate information about the property sell price without going to the location